Correlation between Phenotype and Coagulation Factor Activity Level in Rare Bleeding Disorders: A Systematic Review - Tavasoli, Behnaz; Zangooie, Alireza; Safdari, Seyed Mehrab; Hoseinnezhad, Taraneh; Shabannezhad, Ashkan; Alikhani, Amirreza; Salehi, Zahra; Dorgalaleh, Akbar (Seminars in Thrombosis and Hemostasis, 2024)
Rare bleeding disorders (RBDs) represent 3 to 5% of congenital bleeding disorders and are primarily inherited in an autosomal recessive manner, with increased prevalence in consanguineous populations. Clinically, RBDs can be accompanied by mild to severe bleeding episodes, often assessed using bleeding assessment tools (BATs) such as the International Society on Thrombosis and Hemostasis (ISTH)-BAT. However, the correlation between bleeding severity and coagulation factor activity levels remains inconsistent. This systematic review investigates this relationship to enhance understanding and improve management strategies for patients with RBD. This review adhered to Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines and was registered with the International Prospective Register for Systematic Reviews (PROSPERO) (CRD42024504537). Using the PICO (Population, Intervention, Comparator, and Outcomes) framework, the study focused on RBD patients to explore the correlation between coagulation factor activity levels and bleeding severity. A comprehensive search was conducted across PubMed, Scopus, and Web of Science until April 1, 2024, with data extracted on bleeding severity, phenotype, and coagulation factor activity levels. The analysis highlights complex and often inconsistent relationships between coagulation factor levels and the severity of bleeding. In cases of fibrinogen deficiency, three out of four studies (n = 73 of 111 cases, 66%) demonstrated a moderate to strong correlation between fibrinogen levels and bleeding severity. In prothrombin deficiency, one of two studies (n = 16 of 29 cases, 55%) found a strong correlation between FII levels and bleeding severity. Four of six studies (n = 106 of 139 cases, 76%) in FV deficiency found a weak or no correlation between factor activity and bleeding severity. In combined FV and FVIII deficiency, two of three studies (n = 26 of 60 cases, 43%) found a significant correlation between factor activity and bleeding severity. In FVII deficiency, four (of nine) studies with a study population of 325 patients (65%) found a weak correlation between factor activity and severity of bleeding. Almost all studies (five of six studies, n = 114 of 118 patients, 97%) in FX deficiency revealed a strong correlation between FX levels and bleeding severity. In FXI deficiency, most studies (five of seven studies, n = 254 patients, 93%) found a weak or no correlation between factor activity and bleeding severity or symptoms. For FXIII deficiency, there was a moderate to strong correlation between FXIII activity and bleeding severity in all three studies (n = 61 patients). In conclusion, despite current controversies, this review highlights a moderate or strong correlation between factor activity and bleeding severity in fibrinogen, FX, and FXIII deficiencies, but no correlation or weak correlation for FV, FVII, and FXI deficiencies. Further prospective studies with standardized BATs on a large number of patients are needed to better understand these relationships and optimize patient management.
Keywords: rare bleeding disorders; coagulation factor deficiencies; congenital bleeding disorders; bleeding severity; bleeding phenotype